أثر ممارسات التسويق الداخلي في االداء التسويقي دراسة حالة في مصرف الرافدين ومستشفى أبن االثير في مدينة الموصل - األستاذ المساعد الدكتور نبيل حامد السوّيدي; المدرس المساعد هاسميك انترانيك (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
In this paper we try to demonstrate the impact and relationship between internal marketing and marketing performance. It is attempted to study the reality of interesting sample of Iraqi service organizations (Rafidain Bank and Ibn al-Atheer Hospital) in internal marketing, with group of internal variables that form the main variables, study the impact and relation in details. The main issue is to study the humble interest in employees in Iraqi organizations and how they are the internal customer that have major role in serving the internal customer and gain the profits.We use statistical measurements to analyzing and test data that are been collected using questionnaire distributed on sample of employees works in these two organizations, conclude some points and propose some conclusions.